Investigating steam turbine feasibility to improve the sustainability of a biomass boiler using TRNSYS. (November 2018) - Compton, Marc; Rezaie, Behnaz
Highlights: Study of integration of steam turbine with single and double effect absorption chiller. Fuel consumption, energy efficiency, and exergy efficiency of each case study are calculated. TRNSYS modeling and simulation parallel with exergy modeling are applied. Simulation made six different case studies (winter and summer). Double effect chiller in addition to the single effect chiller has the largest energy efficiency. Abstract: Adding a turbine to a steam generator plant of a district energy system increases the efficiency of the plant by generating some electricity. This is the method of turning a heating and cooling plant into a combined heating, cooling, and power plant. The district energy plant at University of Idaho, Moscow, Idaho, USA is modeled by using TRNSYS modeling software. Simulation of different models is made to compare the current system configuration to the current plus a small backpressure steam turbine, and adding a double effect absorption chiller. Operating costs, energy, and exergy efficiencies are evaluated at current and maximum steam pressure levels through the boiler and turbine. Primary components in the system include a wood chip fired boiler, steam turbine, 2100 kW single effect and 4100 kW double effect absorption chillers, and campus with associated pumping needs. Results show that installing a turbine and increasing pressure to maximum possible levels improve energy and exergy efficiency by 3–4% and 5%, respectively over current levels. Bringing a double effect chiller in addition to the turbine increases energy and exergy efficiencies further to 20% and 7%. Economic savings are substantial if power can be sold back to the utility at a higher rate.